WEB DESIGN E-BEACH CAFÉ PARIAMAN - Dedek Oldio Fernando, Dini Faisal, S.Ds., M.Ds., Henra Afriwan, S.Sn., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
E-beach cafe was established on June 7, 2014 which is located on the Nasri Nasar Pariaman street, sand, Central Pariaman, Pariaman City near the tourist attraction of the Pariaman beach. A better promotion is needed to attract more customers to come to E-Beach Cafe. One of the promotions that can be done is by website media. The purpose of this promotion as a manifestation of the desire of the author so that e-beach cafe has a media promotion in the form of website design that aims to create informative and communicative information media, so that the existence of e-beach cafe can be known to the public.The analysis method used in the promotion of e-beach cafe uses the SWOT analysis method (Strength, Weakness, Opportunities and Threat). The orientation of developing e-beach cafe web design ideas includes the main media in the form of website design and supporting media in the form of menu lists, t-shirts, posters, mugs, x-banners, flagchain, business cards, stickers, and pins. It is expected that with the design of this web design can have promotional media in the form of website media aimed at creating informative and communicative media, so that the existence of e-beach cafes can be known to the public and increased sales turnover from e-beach cafes.Key Words : Design, Web, Website, E-Beach Café.